Early mixing in a Spanish-English simultaneous bilingual in a Japanese context at age 2;4 - Eckhaus, Rebekka (Journal of Monolingual and Bilingual Speech, 2024)
Early language mixing has often been interpreted as bilinguals’ inability to separate languages, although more recent research suggests that young bilingual children have the ability in production. This study analyzes the mixing patterns of Jun, a Spanish-English simultaneous bilingual being raised in a Japanese societal context. Spontaneous speech data have been analyzed from two hours of video recordings, of four family conversations at age 2;4 [years;months], a period at which syntax should be emerging. The investigation found that Jun, prior to acquiring verb inflection, consistently speaks in the context-appropriate language and rarely engages in mixing, suggesting clear language separation and pragmatic sensitivity. Mixing rates, MLU, UB, and monoglossic production in both home languages confirm Jun’s balanced performance, and also language separation. Moreover, the scarcity of inter- and intra-sentential mixing, as well as 1-word mixing, reveals the child’s accommodation to his interlocutors’ language choice, as well as this 2-year-old’s strong control over his own language choice